Hubungan Asupan Kalsium dan Zat Besi dengan Kejadian Dismenore pada Remaja Putri SMA Negeri 1 Boyolangu Tulungagung - Shafarani, Mauletha Putri; Setiyaningrum, Zulia (Politeknik Negeri Jember, 2024)
Dysmenorrhea becomes one of the health problems that can interfere with activities, especially learning activities for adolescent girls. One of the factors causing dysmenorrhea is deficit calcium and iron intake. This study aims to determine the relationship of calcium and iron intake to the incidence of dysmenorrhea in adolescent girls of SMAN 1 Boyolangu Tulungagung. This type of research is analytic observation with cross-sectional design. The number of respondents was 77 respondents which was calculated by Lemeshow 1997 formula. The respondents were determined by simple random sampling technique. Dysmenorrhea data were obtained through face-to-face interviews using the Universal Pain Assessment Tool (UPAT) pain scale questionnaire obtained from the Wong-Baker Faces Foundation. Calcium and iron intake data for the past month were obtained through face-to-face interviews using the Semi Quantitative Food Frequency Questionaire (SQ-FFQ) form and assisted by a food photo book. Calcium and iron intake data were processed with the NutriSurvey application. The collected data were tested using the Spearman Rank test. 92,2% of respondents with deficit calcium intake experienced dysmenorrhea and 75,3% of respondents with deficit iron intake experienced dysmenorrhea. Rank Spearman test between calcium and iron intake with the incidence of dysmenorrhea obtained p-value <0,05. The r value of the Spearman Rank test results for calcium obtained a value of r =-0,893 which means there is a strong negative relationship and for iron obtained a value of r = -0,398 which means there is a weak negative relationship. There is a significant relationship between calcium and iron intake and the incidence of dysmenorrhea in adolescent girls of SMAN 1 Boyolangu Tulungagung.High intake of calcium and iron will reduce the incidence of dysmenorrhea in adolescent girls.